Дано:
<AOB и <COD
<COD внутри <AOB
AO ┴ OD; CO ┴ OB;
<AOB - <COD = 90°
Найти: <AOB и <COD.
Решение
Т.к . AO ┴ OD; CO ┴ OB,
то <AOD = 90°; <COB = 90°.
<COD = <AOD - <AOC
<COD = <COB - <DOB
<COD = 90° - <AOC
<COD = 90° - <DOB
Получим
<AOC = 90° - <COD
<DOB = 90° - <COD
Следовательно <AOC = <DOB
2) По условию: <AOB - <COD = 90°
Но если от всего угла <AOB отнять <COD, то останутся два равных угла <AOC и <DOB, значит, это их сумма равна 90°.
<AOC + <DOB = 90° =>
<AOC = <DOB = 90°/2 = 45°
3) <COD = 90° - <DOB
<COD = 90° - 45°=45°
4) <AOB = <AOC + <DOB + <DOB
<AOB = 45° + 45° + 45° = 135°
ответ: <AOB - 135°; <COD =45°.
Дано:
<AOB и <COD
<COD внутри <AOB
AO ┴ OD; CO ┴ OB;
<AOB - <COD = 90°
Найти: <AOB и <COD.
Решение
Т.к . AO ┴ OD; CO ┴ OB,
то <AOD = 90; <COB = 90°.
<COD = <AOD - <AOC
<COD = <COB - <DOB
<COD = 90° - <AOC
<COD = 90° - <DOB
Получим
<AOC = 90° - <COD
<DOB = 90° - <COD
Следовательно <AOC = <DOB
2) По условию: <AOB - <COD = 90°
Но если от всего угла <AOB отнять <COD, то останутся два равных угла <AOC и <DOB, значит, это их сумма равна 90°.
<AOC + <DOB = 90° =>
<AOC = <DOB = 90°/2 = 45°
3) <COD = 90° - <DOB
<COD = 90° - 45°=45°
4) <AOB = <AOC + <DOB + <DOB
<AOB = 45° + 45° + 45° = 135°
ответ: <AOB - 135°; <COD =45°.
1. (4-6*x)*x*(3*x+2)-8*x+18*x^3=0
2. (4*x-6*x^2)*(3*x+2)-8*x+18*x^3=0
3. 8*x-18*x^3-8*x+18*x^3=0
4. -18*x^3+18*x^3=0
5. 0=0 (доказано)